Performance Analysis of AC Voltage Controller Using Firing Angle and PWM Control for Various Load Conditions - Paudyal, Aayush; Shrestha, Bishesata; Purna Thapa, Nigam (KEC Journal of Science and Engineering, 2026)
This research focuses on the performance analysis of an AC Voltage Controller (ACVC) utilizing various control techniques—specifically firing angle control and Pulse Width Modulation (PWM) control for different load conditions. The AC Voltage Controller is a power electronic device that regulates AC voltage magnitude without altering its frequency. Simulation models were developed using MATLAB/Simulink for resistive, inductive and single-phase induction motor loads under both firing angle and PWM control techniques. The results highlight that PWM control significantly reduces Total Harmonic Distortion (THD) and improves power factor compared to conventional firing angle control, thereby ensuring enhanced performance and efficiency.